PENGARUH BIAYA OPERASIONAL DAN PENDAPATAN BERSIH TERHADAP LABA BERSIH PADA PERUSAHAAN PT BANK NEGARA INDONESIA (BNI) TBK PERIODE 2014 – 2024 - Stepanus Kelvin; Hendri Prasetyo (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to determine the partial and simultaneous effects of operating costs and net income on net profit at PT Bank Negara Indonesia (BNI) Tbk from 2014 to 2024. This study uses a quantitative approach with a sample consisting of the company's financial reports for 11 years. The data analysis techniques employed include descriptive analysis, classical assumption tests, multiple linear regression, and hypothesis testing using t-tests and F-tests with SPSS. The results indicate that, partially, Operating Costs do not significantly affect Net Profit, as shown by the t-value of -0.097 < t-table 2.306 with a significance level of 0.925 > 0.05. Conversely, Net Revenue has a positive and significant effect on Net Profit, with a t-value of 30.085 > t-table 2.306 and a significance level of 0.000 < 0.05. Simultaneously, Operating Costs and Net Revenue have a significant effect on Net Profit, with a t-value of 702.422 > t-table 4.46 and a significance level of 0.000 < 0.05. The coefficient of determination (R²) of 99.4% indicates that the two independent variables can explain 99.4% of the variation in Net Profit.